Comparison of Hormone Therapy with Expectant Management in the Clinical Management of Functional Ovarian Cysts: A Randomized Clinical Trial - Ghasemi, Farah; Mirzaee, Sanaz; Amini, Payam (Advances in Nursing & Midwifery, 2018)
Abstract Hormonal Therapy for functional cysts is widely used in clinical practice, but the efficacy of this treatment has not been determined. The aim of this study was to compare the effect of oral contraceptive with expectant management in treatment of functional ovarian cysts, for this purpose we selected 50 women who came to our clinic as out patients with functional ovarian cysts(between 50 to 95 mm), that those had been identified by vaginal ultrasound, all the patients had stable vital sign, mild to moderate abdominal discomfort. the patients were divided into two equal groups and followed for 8 weeks. The cases were all18_48 years old and subjects with PCO, Dermoid cysts and Endometrioma were excluded for this study. At last 9 patients need surgery because of increasing their symptoms and emergency condition. Group A (n=20) observed without hormonal treatment, only some analgesic if needed and Group B were Received oral contraceptive(n=21). we concluded that expectant management is as effective as oral contraceptive for resolution of functional ovarian cysts .it means the rate of disappearance of functional ovarian cyst was not affected by OCP user. However, studies with a larger number of case are needed to increase the power of results and to obtain a firm conclusion.